The influence of the language style of the anchor on consumers’ purchase intention - Li, Zhen; Zheng, Suqin (Frontiers in Psychology, 2024)
Remarkably, e-commerce anchors have become one of the hot careers in the new media era. As a link between goods and consumers, anchors affect the willingness of consumers to purchase, which eventually impacts the sales volume of commodities in the live broadcast. Therefore, the language style of anchors is of vital significance. However, local and foreign research rarely investigates the interaction between the language style of anchors and different product types and the influential mechanism on consumers’ purchase willingness. In light of the SOR theory’s logic and from the viewpoint of consumer perceived value, this research study scrutinizes the interaction between the language styles of different authors (appealing to emotion and appealing to logic) and different types of products (hedonic products and practical products), as well as the effect mechanism on the consumers’ willingness to purchase. Using questionnaire surveys and empirical analysis, this paper intends to analyze the inherent correlation between study variables, in order to extend valuable suggestions for enterprise practice.